Youtube as a Source of Authentic it Discourse for Esp Learners: A Study on Linus Tech Tips Youtube Channel - Romadhon, Romadhon; Yuliyanti, Novy (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study explores the use of YouTube as a source of authentic Information Technology (IT) discourse for English for Specific Purposes (ESP) learners. The research employs a descriptive qualitative design with documentation and qualitative content analysis methods. The data sources are five selected videos from the channel, chosen purposively based on their relevance to IT topics and pedagogical value. The data collection technique is documentation, where the videos and their transcripts are analyzed using qualitative content analysis. The findings demonstrate that integrating these authentic materials into ESP instruction, through structured pre-viewing, while-viewing, and post-viewing activities, provides significant pedagogical benefits. These include exposing learners to rich technical vocabulary in context, offering multimodal learning experiences, ensuring real-world relevance, and developing listening comprehension and critical thinking skills. Furthermore, the videos enhance learners' awareness of professional discourse norms and facilitate the integration of language and content knowledge, aligning with Content and Language Integrated Learning (CLIL) principles. The study concludes that Linus Tech Tips videos effectively bridge the gap between classroom learning and professional communication, recommending their systematic integration into ESP IT curricula to better prepare students for the linguistic demands of the global technology sector.